The little village of book lovers : a novel - George, Nina, 1973- (Ballantine Books, 2023)
"A young woman with the extraordinary power to bring soulmates together searches for her own true love in this tender, lyrical standalone novel inspired by the "bona fide international hit" (The New York Times Book Review) The Little Paris Bookshop. In Nina George's New York Times bestseller The Little Paris Bookshop, beloved literary apothecary Jean Perdu is inspired to create a floating bookstore after reading a seminal, pseudonymous novel about a young woman with a remarkable gift. Southern Lights is that novel. "Everyone knows me, but none can see me. I am that thing you call Love." In a little town in the south of France in the 1960s, a dazzling encounter with Love itself changes the life of little Marie-Jeanne forever. As a girl, Marie-Jeanne realizes she can see the marks Love has left on the people around her--little glowing lights on the faces and hands that shimmer more brightly when the one meant for them is near. Before long, Marie-Jeanne is playing matchmaker, bringing true loves together in her little town. As she grows up, she helps her father begin a mobile library that travels all throughout the many small mountain towns in the region, and finds herself bringing soulmates together every place they go. In fact, the only person that she can't seem to find a soulmate for is herself. She has no glow of her own, though she waits and waits for it to appear. Everyone must have a soulmate, surely--but will Marie-Jeanne be able to recognize hers when Love finally comes to her?"--